Uncovering myths: A critical reflection of heritage communities and participation - Wischmann, Masja Bentzen (Culture Caleidoscoop, 2024)
In recent years, there has been a shift in heritage policies towards incorporating heritage communities and encouraging participatory practices. However, the concept of ‘community’ often possesses a romantic appeal, leading cultural workers to adopt the notion uncritically. The practice of engaging with communities should not be taken for granted. This contribution explores the very premise of community engagement, offering a critical reflection of the meanings we attach to the concepts of ‘community’ and ‘participation’. Drawing from my field work experience in a Rotterdam community, the article evaluates my own rights and wrongs, exposing the necessity to broaden the understandings of ’community’ and ’participation’. In order to foster a more socially engaged practice, it is essential to challenge one’s own assumptions and biases as cultural workers.